Australian employer perceptions of unprofessional social media behaviour and its impact on graduate employability - Karen Sutherland; Karen Freberg; Christina Driver (Journal of Teaching and Learning for Graduate Employability, 2019)
Social media has become a tool used for the process of employee recruitment in a range of industries. The technology is utilised by job candidates and by employers and job-recruiters to screen and source suitable staff for their organisations. Research has investigated issues relating to ethics, privacy and accuracy regarding employers’ use of social media to screen prospective employees. Yet, limited research has been conducted to investigate employer perceptions of prospective/current employees’ unprofessional social media behavior. Our study involved a survey of 396 Australia employers from a range of industries to explore the influence of job-candidates’ social media presence on employer decision-making and the most unprofessional social media behaviors according to employers. Our investigation found 82% of employers are influenced by a job candidate’s social media presence and using social media to intentionally cause harm to others was perceived by employers as the most unprofessional social media behavior. The findings from this study will assist educators in guiding university students and graduates to meet industry expectations as professionals and provide scholars with new knowledge as to what is deemed to be unacceptable behavior in a professional context at this point in the evolution of social media.